Critically Examining the Person–Environment Relationship and Implications of Intersectionality for Participation in Children's Rehabilitation Services - Reitzel, Meaghan; Letts, Lori; Di Rezze, Briano; Phoenix, Michelle (Frontiers in Rehabilitation Sciences, 2021)
Children’s participation in rehabilitation services is associated with positive functional and developmental outcomes for children with disabilities. Participation in therapy is at risk when a child’s personal and environmental contexts create barriers to accessing services. The International Classification of Functioning, Disability and Health (ICF) provides a framework for conceptualizing the personal and environmental factors linked to a child. However, it does not facilitate critical examination of the person-environment relationship and its impact on participation in children’s rehabilitation. This perspective paper proposes the use of intersectionality theory as a critical framework in complement with the ICF to examine the impact of systemic inequities on participation in therapy for children with disabilities. Clinicians are called to be critical allies working alongside children and families to advocate for inclusive participation in children’s rehabilitation by identifying and transforming systemic inequities in service delivery.